The Role of Good Corporate Governance as a Moderating Variable in Relationship Between Solvency, Company Size, Liquidity and Stock Price - Hermiyetti Hermiyetti; Rina Apriliani; Muhammad Hery Santoso; Murwani Wulansari; Agoes Hadi Poernomo (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to see how liquidity, solvency, firm size, and corporate governance (GCG) affect consumer goods industrial sector businesses listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. This research employs multiple linear regression analysis with secondary data from the company's financial statements and annual reports. The current ratio, debt to equity, firm size, and corporate governance (GCG) are used as independent factors in this study, with stock prices as the dependent variable and corporate governance (GCG) as the moderating variable. According to the findings of this study, the Current Ratio (CR) and Debt to Equity Ratio (DER) have a partially negative and substantial influence on stock prices, and concurrently independent factors have a significant effect on stock prices using the previous year’s stock price as a control variable. Meanwhile, stock prices are unaffected by business size or GCG. And GCG, as a moderating variable, cannot increase the company’s size.